2014
DOI: 10.1093/humrep/deu024
|View full text |Cite
|
Sign up to set email alerts
|

Hysterosalpingosonography for diagnosing tubal occlusion in subfertile women: a systematic review with meta-analysis

Abstract: This review has been registered at PROSPERO: Registration number #CRD42013003829.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 44 publications
1
60
3
1
Order By: Relevance
“…In a recently published meta-analysis about 2D-HyCoSy by Maheux-Lacroix et al [7,] they found that pooled sensitivity and specificity for 2D-HyCoSy were 88% (95% CI 80-94) and 92% (95% CI 87-95), respectively. Looking at 95% CIs, and comparing with our data, we could roughly derive that 3D-HyCoSy seems more sensitive that 2D-HyCoSy for detecting tubal occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published meta-analysis about 2D-HyCoSy by Maheux-Lacroix et al [7,] they found that pooled sensitivity and specificity for 2D-HyCoSy were 88% (95% CI 80-94) and 92% (95% CI 87-95), respectively. Looking at 95% CIs, and comparing with our data, we could roughly derive that 3D-HyCoSy seems more sensitive that 2D-HyCoSy for detecting tubal occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews and meta-analyses assessing the diagnostic performance of 2D-HyCoSy for diagnosing tubal occlusion in women with subfertility have been published so far [6,7]. Both studies proved that 2D-HyCoSy was a sensitive and specific procedure to evaluate tubal patency.…”
Section: Introductionmentioning
confidence: 99%
“…A previous meta-analysis with most 2D HyCoSy studies showed that the sensitivity and specificity of 2D HyCoSy were, 0.88 (95% CI: 0.80-0.94) and 0.92 (95% CI: 0.86-0.96), respectively. 8 For the sensitivity and specificity of 2D HyCoSy significantly overlapped with 3D/4D HyCoSy, the variation of sensitivity and specificity among different dimensional HyCoSy has not yet been determined. However, some limitations and difficulties of conventional 2D HyCoSy are often encountered in clinical operation.…”
Section: Subgroup Analyses and Publication Biasmentioning
confidence: 99%
“…A meta-analysis with most two-dimensional (2D) HyCoSy studies showed that HyCoSy was better than hysterosalpingography in diagnosing tubal occlusion and should be in the initial work-up of subfertile couples. 8 In recent years, with the development of ultrasound imaging technology, threedimensional (3D) or four-dimensional (4D) HyCoSy is widely studied in the diagnostic work-up of infertile females. However, the results of each study for 3D/4D HyCoSy were inconsistent [9][10][11][12] and the inadequate sample size in the individual study could not attain the precise outcome.…”
Section: Introductionmentioning
confidence: 99%
“…1 FemVue specifically uses a device that simultaneously injects air and saline solution in a controlled fashion while ultrasonography imaging documents intratubal flow. 2 Hysterosalpingocontrast sonography as a diagnostic technique has been available since the early 1980s but has increased in popularity in the last 10 to 12 years.…”
Section: Discussionmentioning
confidence: 99%